Cultural Geomorphology as an Attraction to Promote Geotourism (Case Study: Neyshabur and Firuzeh Counties) - Maryam Daemi; Neda Torabi Farsani; Reza Khoshraftar (Geoconservation Research, 2022)
Surface topography is involved with cultural values in some destinations, and Neyshabur and Firuzeh Counties constitute good examples. In this paper, we present the primary geosites with cultural geomorphology values and aims to investigate the appropriate solutions for promoting geotourism with an emphasis on cultural geomorphology. Thematic analysis as a qualitative method and observation was used, and the results demonstrated that Neyshabur and Firuzeh counties include 19 geosites with cultural geomorphology values. We propose the use of marketing, government support, research and identification, local empowerment, and development of new products and services to offer to tourists with geo-themes as key solutions to promote geotourism with an emphasis on cultural geomorphology.